تصمیم الخدمات المعلوماتیة وفقا لاحتیاجات المستفیدین من مکتبات کلیات جامعة طنطا : دراسة تخطیطیة - د. هبة فتحى دنیا (المجلة الدولية لعلوم المكتبات والمعلومات)
The study aimed to adopt analytical and planning frameworks for theimplementation of future information services based on the needs of current andpotential users from the libraries of Tanta University. This is based on theanalytical descriptive approach, with the adoption of a method of content analysisto collect and analyze data and to help plan a comprehensive framework for thedevelopment of library services at Tanta University.The questionnaire was used as a data collection tool, which wasdistributed to a sample of faculty members and students of the faculties of TantaUniversity to survey their views on their needs for information services and toidentify their future vision. And survey of a sample of international universitieslibraries that Design User Centered Services, to identify these services.The study concluded that the libraries of international universities havedistinguished in services such as scientific publishing and Internet services andsupporting information literacy, Users of libraries in Tanta University need toactivate the role of the college libraries through the provision of internet servicesand other Electronic services.The study provided planning for the design of these services and othersaccording to the needs of users. The study also concluded that costs, the need toqualify human in libraries, limited library space, and lack of technology are themost important challenges that may face the faculties of the University of Tantalibraries when adopting this approach.